The witch tree symbol - Keene, Carolyn (New York : Grosset & Dunlap, 2006)
An unusual hex sign leads Nancy Drew to Pennsylvania Dutch country in pursuit of a thief who stops at nothing to get rid of her.
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Amish -- Fiction; Detective and mystery stories, American